Surgical outcomes of gastroenterological surgery in Japan: Report of the National Clinical Database 2011‐2017. Issue 4 (20th May 2019) - Hasegawa, Hiroshi; Takahashi, Arata; Kakeji, Yoshihiro; Ueno, Hideki; Eguchi, Susumu; Endo, Itaru; Sasaki, Akira; Takiguchi, Shuji; Takeuchi, Hiroya; Hashimoto, Masaji; Horiguchi, Akihiko; Masaki, Tadahiko; et al.
Abstract: Background: The Japanese National Clinical Database (NCD) is a large‐scale, nationwide, web‐based data entry system that is linked to the surgical board certification system and covers almost all surgical cases carried out in Japan. Aim: To evaluate outcomes according to the gastroenterological section of the NCD. Methods: The 115 surgical procedures stipulated by the "Training Curriculum for Board‐Certified Surgeons in Gastroenterology" were registered from 2011 to 2017. The number of surgeries, preoperative comorbidities, and short‐term outcomes were compared between registration periods. Results: In total, 3 818 414 cases have been registered. More than 70% of all surgeries were carried out at certified institutions. The annual number of cases has been increasing year after year, and the aged population has also been increasing. Although the rates of preoperative comorbidities and postoperative complications have been increasing, the postoperative mortality rate has remained relatively low; in 2017, the 30‐day mortality rate was 1.0% among those who underwent esophagectomy, 0.7% among those who underwent distal gastrectomy, 1.1% among those who underwent total gastrectomy, 1.3% among those who underwent right hemicolectomy, 0.5% among those who underwent low anterior resection, 1.3% among those who underwent hepatectomy, and 1.3% among those who underwent pancreaticoduodenectomy. The annual rate of endoscopic surgery dramatically increased over 7 years between 2011 and 2017, especially for low anterior resection (29.5%‐62.6%) and esophagectomy (31.0%‐56.1%). Conclusion: This database is expected to ensure the quality of the board‐certification system and surgical outcomes in gastroenterological surgery. Abstract : NCD Annual Report‐2017.